Islamic Business Ethics in Palm Oil Trading: Evidence from Farmer–Collector Transactions in Binanga Dua Village, Indonesia - Lian Diza Loriva Siregar; Rahmat Daim Harahap; Tri Inda Fadhila Rahma (Jurnal Investasi Islam, 2026)
This study aims to analyze the implementation of Islamic business ethics in palm oil trading practices in Binanga Dua Village, South Labuhanbatu Regency, North Sumatra. The study addresses the limited empirical research on the application of Islamic business ethics within rural palm oil supply chains, particularly in the relationship between farmers and collector agents. Binanga Dua Village was selected because most independent farmers depend on collectors due to limited transportation, market access, and bargaining power. This study employed a descriptive qualitative approach using purposive sampling involving seven informants representing farmers, collector agents, community leaders, and village officials. Data were collected through observation, semi-structured interviews, and documentation and were analyzed using the Miles and Huberman interactive model, including data condensation, data display, thematic coding, and conclusion drawing. The findings indicate that trust (amanah), mutual assistance (ta’awun), and immediate cash payment practices have been implemented in trading activities. However, the study also identified limited transparency in the weighing process, asymmetric price information, and weak bargaining power among farmers, which reduce the realization of justice (‘adl) and transparency (tabligh). This study contributes to the development of applied Islamic business ethics by providing empirical evidence for improving ethical governance and promoting a fairer and more sustainable rural palm oil supply chain.